RESEARCH AND MODELING OF FLUID MOTION IN THE CASE WHEN THE VOLUME OF THE FLUID DOES NOT CHANGE AND IN THE CASE WHEN THE VOLUME CHANGES - Abdymanapov, S.A.; Kassenova, L.G. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
A liquid is a physical body that has the property of fluidity, so it does not have its own shape and takes the form of a vessel that it fills. Liquids are divided into two types: drip and gaseous. Droplet liquids are characterized by high compression resistance (almost complete incompressibility) and low resistance to tensile and tangential forces, due to the insignificance of the coupling forces and friction forces between the liquid particles. An incompressible fluid is a mathematical model of a continuous medium whose density is preserved when the pressure changes. When defining an incompressible liquid, it is assumed that it retains the basic properties of the liquid, in particular, to change shape at a constant volume. The article presents the experiments demonstrating two types of incompressible fluid are presented. The first type is the motion of fluid not changing its volume due to elastic deformation. The second type is the formation of vortices during the expansion of the fluid that has received additional kinetic energy. Formulas for calculating and modeling vortices are proposed.